Phylogenomic resolution of the root of panpulmonata, a hyperdiverse radiation of gastropods: new insight into the evolution of air breathing - Krug, Patrick J.; Caplins, Serena A.; Algoso, Krisha; Thomas, Kanique; Valdés, Ángel A.; Wade, Rachael; Wong, Nur Leena W. S.; Eernisse, Douglas J.; Kocot, Kevin M. (The Royal Society, 2022)
Transitions to terrestriality have been associated with major animal radiations including land snails and slugs in Stylommatophora (>20 000 described species), the most successful lineage of ‘pulmonates’ (a non-monophyletic assemblage of air-breathing gastropods). However, phylogenomic studies have failed to robustly resolve relationships among traditional pulmonates and affiliated marine lineages that comprise clade Panpulmonata (Mollusca, Gastropoda), especially two key taxa: Sacoglossa, a group including photosynthetic sea slugs, and Siphonarioidea, intertidal limpet-like snails with a non-contractile pneumostome (narrow opening to a vascularized pallial cavity). To clarify the evolutionary history of the panpulmonate radiation, we performed phylogenomic analyses on datasets of up to 1160 nuclear protein-coding genes for 110 gastropods, including 40 new transcriptomes for Sacoglossa and Siphonarioidea. All 18 analyses recovered Sacoglossa as the sister group to a clade we named Pneumopulmonata, within which Siphonarioidea was sister to the remaining lineages in most analyses. Comparative modelling indicated shifts to marginal habitat (estuarine, mangrove and intertidal zones) preceded and accelerated the evolution of a pneumostome, present in the pneumopulmonate ancestor along with a one-sided plicate gill. These findings highlight key intermediate stages in the evolution of air-breathing snails, supporting the hypothesis that adaptation to marginal zones played an important role in major sea-to-land transitions.